2010
DOI: 10.1149/1.3485274
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced ALD of TiO2 Using a Novel Cyclopentadienyl Alkylamido Precursor [Ti(CpMe)(NMe2)3] and O2 Plasma

Abstract: Titanium oxide thin films of both amorphous and anatase morphologies have been deposited using remote plasma ALD over a wide temperature range (100-350 °C), using a novel heteroleptic alkylamido precursor Ti(Cp Me )(NMe 2 ) 3 . A high growth per cycle (GPC) of 0.07-0.08 nm (which is about 50 % higher than the GPC obtained with most other organometallic precursors) without any nucleation delay was observed. Rutherford backscattering (RBS) and X-ray photoelectron spectroscopy (XPS) studies on the deposited films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Between the two steps, the chamber was purged for 2 s with argon flow. The heteroleptic titanium precursor was chosen due to the higher growth per cycle (GPC) in comparison with other most common precursors, i.e., the homoleptic tetraisopropoxide (TTIP) (Potts et al, 2010;Sarkar et al, 2010). At 150 °C, the GPC of the process was 0.055 nm/cycle compared to 0.04 nm/cycle measured for the process with TTIP precursor.…”
Section: Tio 2 Compact Layersmentioning
confidence: 99%
“…Between the two steps, the chamber was purged for 2 s with argon flow. The heteroleptic titanium precursor was chosen due to the higher growth per cycle (GPC) in comparison with other most common precursors, i.e., the homoleptic tetraisopropoxide (TTIP) (Potts et al, 2010;Sarkar et al, 2010). At 150 °C, the GPC of the process was 0.055 nm/cycle compared to 0.04 nm/cycle measured for the process with TTIP precursor.…”
Section: Tio 2 Compact Layersmentioning
confidence: 99%
“…The TiO 2 compact layers were deposited on conductive substrate (ITO-PET) at 150 o C in a thermal and remote plasma reactor (FlexAL TM ) using heteroleptic dimethylamido precursor with a methylcyclopentadienyl ligand (Ti(Cp Me )(NMe 2 ) 3 an O 2 inductively coupled plasma. Details and specifications of the ALD process have been extensively discussed in (22). A -plasma treatment (200W) of 3 min was performed prior to the ALD deposition.…”
Section: Methodsmentioning
confidence: 99%
“…opto-electrical, crystallographic and mechanical) properties of the deposited layer [41][42][43] by tuning the composition of the gas feeding the plasma. Other parameters which contribute to control the properties of the layers are the plasma power, the plasma exposure time and the applied bias at the substrate where deposition occurs [44][45][46][47][48][49]. As an example, Profijt et al have shown that the crystal structure of TiO 2 can be tuned from anatase to rutile by varying the bias applied on the substrate holder [45].…”
Section: Introductionmentioning
confidence: 99%